Hybrid Feedback Compensation of an External Capacitor-less Low Dropout Voltage Regulator - Gitzel, Daniel; Silva-Martinez, Jose; Rivera, Rafael (Columbia Undergraduate Research Journal, 2014)
Power management has an ever increasing presence in the electronics industry due to the growth of battery powered mobile devices. The low-dropout voltage regulator (LDO) offers improved efficiency over other regulator topologies. However, the architecture suffers from stability issues, which usually necessitates a large off-chip capacitor to ensure the regulator’s performance. This paper presents an alternative topology by removing the bulky external capacitor, thus allowing for greater power system integration. The proposed Current Amplifier Hybrid Compensation (CAHC) scheme implements an active feedback-feedforward compensation system and maintains both a fast transient response and full range alternating current (AC) stability from 0 to 50mA load currents even with a 100pF loading capacitance. The 1.2V External Capacitor-less LDO voltage regulator was designed and simulated in a commercial 0.35um CMOS technology, consuming only 61uA of quiescent current with a dropout voltage of less than 200mV. Simulated results demonstrate that the proposed External Capacitor-less LDO architecture overcomes the typical load transient and AC stability issues encountered in previous architectures. The combined size and component reduction of this architecture presents a more integrable and economic power management system.